2021
DOI: 10.2196/28845
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inpatient Telemedicine on Personal Protective Equipment Savings During the COVID-19 Pandemic: Cross-sectional Study

Abstract: With the emergence of the COVID-19 pandemic and shortage of adequate personal protective equipment (PPE), hospitals implemented inpatient telemedicine measures to ensure operational readiness and a safe working environment for clinicians. The utility and sustainability of inpatient telemedicine initiatives need to be evaluated as the number of COVID-19 inpatients is expected to continue declining. In this viewpoint, we describe the use of a rapidly deployed inpatient telemedicine workflow at a large academic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(29 reference statements)
0
5
0
Order By: Relevance
“… [12] , [13] , [14] , [15] These studies demonstrated several advantages to these types of systems, including minimizing provider exposure [6] and managing surge capacity [16] as well as potential drawbacks such as device connectivity issues [12] , difficulty performing physical exams [17] , and variability in patient receptiveness to telemedicine. [12] While some recent evidence has cast doubt upon if inpatient telemedicine truly conserves PPE [18] , several studies have described innovative approaches to emergency care using telemedicine which have blossomed from improved telemedicine infrastructure including monitoring of high-risk discharged patients [19] , remote consults to the ED [20] , or training of new providers. [21] This study moves beyond simply describing the implementation process and begins to examine how telemedicine actually impacts clinical process metrics within the ED considering the changes in clinical workflow that telemedicine necessitates.…”
Section: Discussionmentioning
confidence: 99%
“… [12] , [13] , [14] , [15] These studies demonstrated several advantages to these types of systems, including minimizing provider exposure [6] and managing surge capacity [16] as well as potential drawbacks such as device connectivity issues [12] , difficulty performing physical exams [17] , and variability in patient receptiveness to telemedicine. [12] While some recent evidence has cast doubt upon if inpatient telemedicine truly conserves PPE [18] , several studies have described innovative approaches to emergency care using telemedicine which have blossomed from improved telemedicine infrastructure including monitoring of high-risk discharged patients [19] , remote consults to the ED [20] , or training of new providers. [21] This study moves beyond simply describing the implementation process and begins to examine how telemedicine actually impacts clinical process metrics within the ED considering the changes in clinical workflow that telemedicine necessitates.…”
Section: Discussionmentioning
confidence: 99%
“…This novel use of inpatient telemedicine is still being explored: in one academic medical setting, the technology was broadly accepted by clinicians and staff but required nurses to drastically alter their workflow practices [ 27 ]. In another setting, in-room video technology saw the greatest adoption among patients who used it to communicate with their loved ones [ 28 ]. Little else is formally known about how patients perceive inpatient telemedicine, particularly under isolation conditions that a COVID-19 diagnosis necessitates.…”
Section: Introductionmentioning
confidence: 99%
“…In the inpatient setting, telehealth was previously used to connect hospitalized patients in rural settings with remote specialists [ 3 ], but has recently expanded to facilitate digital communication between patients and on-site clinicians [ 4 - 6 ]. The impact of inpatient telehealth on infection reduction [ 7 ], clinical workflows [ 8 , 9 ], patient safety [ 10 ], and personal protective equipment (PPE) utilization [ 10 , 11 ] is still under investigation. In the context of a pandemic, telehealth’s impact on infection control and clinical care is of particular interest, although existing evaluations have relied on PPE inventory data and patient and provider satisfaction surveys [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of inpatient telehealth on infection reduction [ 7 ], clinical workflows [ 8 , 9 ], patient safety [ 10 ], and personal protective equipment (PPE) utilization [ 10 , 11 ] is still under investigation. In the context of a pandemic, telehealth’s impact on infection control and clinical care is of particular interest, although existing evaluations have relied on PPE inventory data and patient and provider satisfaction surveys [ 10 , 11 ]. However, the expanding use of real-time locator systems (RTLSs), as an objective source of location and time data, in inpatient settings offers a unique opportunity to understand how clinical workflows adapt to these novel circumstances.…”
Section: Introductionmentioning
confidence: 99%